2021
DOI: 10.1177/1362361321998573
|View full text |Cite
|
Sign up to set email alerts
|

Autistic differences in the temporal dynamics of social attention

Abstract: Individuals with autism spectrum disorders typically exhibit reduced visual attention towards social stimuli relative to neurotypical individuals. Importantly, however, attention is not a static process, and it remains unclear how such effects may manifest over time. Exploring these momentary changes in gaze behaviour can more clearly illustrate how individuals respond to social stimuli and provide insight into the mechanisms underlying reduced social attention in autism spectrum disorder. Using a simple passi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 57 publications
2
19
1
Order By: Relevance
“…Importantly, divergence analyses, performed to determine the exact moments in which groups diverged from each other, demonstrated that individuals with ASD showed significantly reduced social attention towards the middle of the stimulus presentation compared to controls, while BAP(+) parents showed a later divergence from control parents, occurring towards the second half, and an even more dramatic decline in attention to social AOIs in the final seconds of the stimulus presentation, compared to both control parents and BAP(−) parents. These findings converge with prior literature examining temporal dynamics of social attention among adults with ASD relative to controls [ 61 , 62 ]. Both studies found a decrease of social attention among adults with ASD relative to controls, who instead looked away from social information initially but returned their attention back to social information towards the end of the stimulus presentation.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Importantly, divergence analyses, performed to determine the exact moments in which groups diverged from each other, demonstrated that individuals with ASD showed significantly reduced social attention towards the middle of the stimulus presentation compared to controls, while BAP(+) parents showed a later divergence from control parents, occurring towards the second half, and an even more dramatic decline in attention to social AOIs in the final seconds of the stimulus presentation, compared to both control parents and BAP(−) parents. These findings converge with prior literature examining temporal dynamics of social attention among adults with ASD relative to controls [ 61 , 62 ]. Both studies found a decrease of social attention among adults with ASD relative to controls, who instead looked away from social information initially but returned their attention back to social information towards the end of the stimulus presentation.…”
Section: Discussionsupporting
confidence: 89%
“…Spatial Distribution Analysis or Nearest Neighbor Index (i.e., distance-dispersion algorithm) were also examined in children with and without ASD, to explore how fixations were dispersed across the facial stimuli [ 60 ]. Finally, growth curve analyses (GCA), proves to be a rigorous method of assessing changes over the course of time, which can be applied to understand the moment-to-moment pattern of gaze while interpreting a scene [ 61 , 62 ]. In particular, GCA maps out the time-linked gaze trajectory over the course of the stimulus presentation and can elucidate changes occurring longitudinally across developmental time periods, such as those found in infants with and without ASD [ 63 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, diagnostic group differences were apparent because the social attention of typical peers recovers periodically such that alternating attention to and from a social partner is the typical pattern. This pattern of recovery and alternation of attention to faces is significant less robust in ASD (93,94). Processes related to alternating between social and non-social attention are also thought to be a critical component of early joint attention development, especially IJA [ (41,95), see Figure 2].…”
Section: The Timing Of the Development Of Social Orienting And Joint Attention Symptomsmentioning
confidence: 99%
“…It could reflect the gradual onset of an attenuation of processes associated with spontaneously social orienting to faces across early development. However, studies of the temporal dynamics of social attention indicate that individuals with both ASD and typically developing children orient to faces comparably and also display a decay, or habituation of attention to faces over time ( 93 , 94 ). However, diagnostic group differences were apparent because the social attention of typical peers recovers periodically such that alternating attention to and from a social partner is the typical pattern.…”
Section: The Timing Of the Development Of Social Orienting And Joint ...mentioning
confidence: 99%
“…Taken together, these results suggest that low investigation times are not the result of global behavioral inhibition. Low investigation of a novel social stimulus may represent a number of specific deficits, including faulty recognition of a novel stimulus as familiar, inattention to social stimuli, reduced motivation/reward associated with social stimuli, and/or inability to recognize social novelty, all of which have been reported in humans with ASD (Guillory et al, 2021; Hedger and Chakrabarti, 2021; Aldridge-Waddon et al, 2020; Weigelt et al, 2012; Chevallier et al, 2012). More specifically related to the Shank3B mouse model, individuals diagnosed with both Phelan-McDermid syndrome and ASD exhibit reduced social attention and reduced social novelty recognition under certain conditions (Guillory et al, 2021).…”
Section: Discussionmentioning
confidence: 99%